Effect of gangue distributions on cutting force and specific energy in coal cutting - Jiang, Kao (Strojniški vestnik, 2020)
Coal consists of diverse materials, and gangue is one of the most common ones. At present, most mathematical models about cutting force and specific energy in the cutting process have not taken gangue minerals in coal seams into consideration. The gangue distribution function is proposed to simulate situations in which gangue minerals are in different distributions. Moreover, the cutting force due to gangue mineral at different heights is also obtained with the finite element method. Combined with the gangue distribution function, the increased cutting force due to gangue minerals can be obtained for any gangue distribution. The present paper also proposes a new mathematical model to calculate the increased specific energy under different gangue distributions. The results show that the gangue distribution function is useful for simulating various situations of gangue distributions in coal seams. Under dispersive gangue distribution in coal seams, the increased mean cutting force, as well as the increased specific energy, is less influenced by gangue distribution, and it tends to be a constant. These results can be useful for the related research on coal cutting under complicated conditions.
Keywords: cutting force; eno rezalno orodje; gangue distributions; Gaussova porazdelitvena funkcija; jalovina; porazdelitev jalovine; rezalna sila; single cutter; specific energy; specifična poraba energije